2020
DOI: 10.3390/ijerph17061827
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with High Mercury Levels in Women and Girls from The Mojana Region, Colombia, 2013–2015

Abstract: Women are primarily exposed to mercury through the consumption of fish contaminated by gold mining activities. The main systems affected are the central nervous and renal systems, although effects on the reproductive system have also been found. Objective: To explore the relationship between mercury levels in women and their possible sources of contamination. A cross-sectional study was conducted from 2013 to 2015 with women residing in 11 municipalities in La Mojana, Colombia, using non-random sampling. Stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Comparing this study results with previous research, similar Hg levels were found with other communities in the Amazon region [ 30 , 31 , 36 , 38 , 39 , 40 , 41 ] and in South America [ 42 , 43 , 44 , 45 , 46 ], all exceeding internationally accepted safety levels for total Hg in hair [ 1 ].…”
Section: Discussionsupporting
confidence: 89%
“…Comparing this study results with previous research, similar Hg levels were found with other communities in the Amazon region [ 30 , 31 , 36 , 38 , 39 , 40 , 41 ] and in South America [ 42 , 43 , 44 , 45 , 46 ], all exceeding internationally accepted safety levels for total Hg in hair [ 1 ].…”
Section: Discussionsupporting
confidence: 89%
“…We also noticed that about 82% of the volunteer exceed the USEPA recommended limit [32], whereas 56% of the sampled group exceed the normal level of WHO [31]. The percentage of unhealthy levels of mercury (above 6 μg Hg/gram of hair by WHO standards [39] [40] [41], concerned 2% of the population with 50% for each village.…”
Section: Mercury Concentration In Hairmentioning
confidence: 89%
“…The values obtained in Córdoba department (Calao-Ramos et al, 2021;Gracia et al, 2010Gracia et al, , 2016Marrugo-Negrete et al, 2013) could be compared with those obtained from Antioquia, Sucre (Argumedo et al, 2013;Olivero-Verbel et al, 2016) and Bolívar (Carranza-Lopez et al, 2019;Olivero-Verbel et al, 2011;Olivero et al, 1995) regions, as these four regions are adjacent, and some of their territories conform the Mojana region (Diaz et al, 2020) (Fig. S5).…”
Section: Comparison With Other Colombian Studiesmentioning
confidence: 96%